Analysis of Maros River Discharge Using the Modified Soil and Water Assessment Tools (SWAT) Program - Ahmad Fausan; Asep Sapei; Yuli Suharnoto; Nora Herdiana Pandjaitan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Soil and Water Assessment Tools (SWAT) which is developed in America was used to analyze the effect of land management on discharge, sedimentation, and water quality in a river basin area. The hydrological conditions in the Americas are different from Indonesia, so a modified SWAT is done. This research aimed to implement a modified SWAT program to predict the results of a better discharge analysis based on hydrological analysis in the sub-Watershed area. About 13.90% of the area was paddy fields. The evaluation of the module had been done by looking at the coefficient of determination (R²) and Nash-Sutcliffe Efficiency (NSE) based on the comparison of simulated discharge results with an observation discharge. Research began with delineation DEM, HRU formation, simulation, calibration, and validation. The R² value for daily data on modified SWAT was 0,725. It was better than the original SWAT and SWAT with Pothole, which were 0,706 and 0,708 respectively. Likewise, the NSE value for daily data on modified SWAT was 0,721, on original SWAT and on SWAT with Pothole was 0,668 and 0,685 respectively. The analysis result showed that the modified SWAT provide good discharge prediction results, indicated by relatively high R2 and NSE values.Keywords: hydrological analysis,modified SWAT, paddy field, pothole, SWAT